New Mobility in Everyday Life - Perspectives From 20 Households Examined Over Four Months - Jannis Linke; Philipp Scharfenberger; Jürgen Stackmann (Marketing Review St.Gallen, 2023)
The study examines the experiences of 20 households adapting their mobility behaviour with the goal of lower-emission mobility over four months, using, e.g., shared mobility products. The results of 13 targeted interventions are described and combined into three key perspectives that need to be considered when developing lower-emission future mobility products.
Keywords: 650